Thrombosis and Embolism: from Research to Clinical Practice : Volume 1 - Islam, Md. Shahidul (Springer International Publishing : Imprint: Springer, 2017)
This unique publication explores diverse themes relating to thrombosis and embolism, from basic research at cell and molecular level to the actual care, prevention, and treatment of diverse categories of patients suffering from such diseases. Chapters cover a variety of topics including thrombosis and embolism in surgical patients, cancer patients, pregnant women and children and adolescents, as well as treatment of the conditions by traditional anticoagulants, novel oral anticoagulants, thrombolytic therapy, endovascular treatment and embolectomy. Readers may explore cutting edge research, recommendations from major societies, contemporary guidelines, areas of controversy and directions for ongoing and future research. The book features comprehensive information ranging from molecular mechanisms of diseases to the clinical features, diagnosis, and therapeutic regimens for treating a variety of clinical conditions. It has a broad appeal to scientists and research students as well as busy clinicians engaged in patient care, who will all find something important and useful amongst these carefully selected chapters.- Resumé vydavatel
Keywords: trombóza; embolie; antikoagulancia; kardiovaskulární nemoci; thrombosis; embolism; anticoagulants (medicine); cardiovascular diseases; elektronické knihy; kolektivní monografie; electronic books; collective monographs